Lattice Discontinuities of 1T-TaS2 across First Order Charge Density Wave Phase Transitions - Wang, Wen; Dietzel, Dirk; Schirmeisen, André; Justus Liebig University Giessen (My University, 2019)
Transition metal dichalcogenides are lamellar materials which can exhibit unique and remarkable electronic behavior due to effects of electron-electron and electron-phonon coupling. Among these materials, 1T-tantalum disulfide (1T-TaS2) has spurred considerable interest, due to its multiple first order phase transitions between different charge density wave (CDW) states. In general, the basic effects of charge density wave formation in 1T-TaS2 can be attributed to in plane re-orientation of Ta-atoms during the phase transitions. Only in recent years, an increasing number of studies has also emphasized the role of interlayer interaction and stacking order as a crucial aspect to understand the specific electronic behavior of 1T-TaS2, especially for technological systems with a finite number of layers. Obviously, continuously monitoring the out of plane expansion of the sample can provide direct inside into the rearrangement of the layer structure during the phase transition. In this letter, we therefore investigate the c-axis lattice discontinuities of 1T-TaS2 by atomic force microscopy (AFM) method under ultra-high vacuum conditions. We find that the c-axis lattice experiences a sudden contraction across the nearly-commensurate CDW (NC-CDW) phase to commensurate CDW (C-CDW) phase transition during cooling, while an expansion is found during the transition from the C-CDW phase to a triclinic CDW phase during heating. Thereby our measurements reveal, how higher order C-CDW phase can favor a more dense stacking. Additionally, our measurements also show subtler effects like e.g. two expansion peaks at the start of the transitions, which can provide further insight into the mechanisms at the onset of CDW phase transitions.
Keywords: ddc:530